2017
DOI: 10.1177/2325967117741647
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Body Checking on Youth Ice Hockey Injuries

Abstract: Background:Body checking is a common cause of youth ice hockey injuries. Consequently, USA Hockey raised the minimum age at which body checking is permitted from the Pee Wee level (11-12 years old) to the Bantam level (13-14 years old) in 2011.Purpose/Hypothesis:The purpose of this investigation was to determine the impact of body checking on the distribution of injuries reported in youth ice hockey players. We hypothesized that the elimination of body checking at the Pee Wee level would lower the frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
(32 reference statements)
0
14
0
1
Order By: Relevance
“…Six of the 33 included studies evaluated the effects of implementing national sports rules and/or policy changes. 42,43,57,64,65,70 Body checking among Pee Wee (11-12 years old) ice hockey players has been banned in Canada 42 and the USA 65 nationally. The USA implemented this policy change in 2011, demonstrating a 38.2% decrease in body checking injuries.…”
Section: Sports Rules and Policy Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the 33 included studies evaluated the effects of implementing national sports rules and/or policy changes. 42,43,57,64,65,70 Body checking among Pee Wee (11-12 years old) ice hockey players has been banned in Canada 42 and the USA 65 nationally. The USA implemented this policy change in 2011, demonstrating a 38.2% decrease in body checking injuries.…”
Section: Sports Rules and Policy Changesmentioning
confidence: 99%
“…The USA implemented this policy change in 2011, demonstrating a 38.2% decrease in body checking injuries. 65 Canada followed in 2013 leading to a 50% reduction in body checking injuries and a 64% reduction in concussion rates. 42 Conversely, the USA policy change saw a 50% increase in concussions in the Pee Wee players, with the authors hypothesizing that increased head-to-ice contacts and increased concussion awareness among players were possible mechanisms for this rise.…”
Section: Sports Rules and Policy Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…To this point, in 2011, USA Hockey raised the minimum age that body checking is permitted from 11–12 years (Pee Wee) to 13–14 years (Bantam level) [4]. To examine the issue of player safety and checking in youth ice-hockey, numerous epidemiological studies have been performed, but the results have been equivocal [5, 6]. Some studies reported that decreasing age of exposure to checking increased the odds of injury [7], while other studies found no significant change to injury rates with an increase to the minimum checking age [8].…”
Section: Introductionmentioning
confidence: 99%
“…Takođe je bitno obratiti pažnju i na razlike u povređivanju u odnosu na pol i starost (4), odnosno u odnosu na vrstu sporta, jer svaki sport ima svoje specifičnosti zbog većeg angažovanja određene grupe mišića i delova koštano-zglobnog sistema usled repetitivnog ponavljanja određenog pokreta (5)(6)(7)(8) …”
unclassified